A Critical Examination of Mindblindness as a Metaphor for Autism. (29th January 2013) - Dinishak, Janette; Akhtar, Nameera
Abstract Metaphor—describing one thing in terms of another—is a common tool used to grasp what is unknown. Perhaps because we do not understand a lot about autism, many metaphors appear in both scientific and nonscientific descriptions of autism. The metaphor of mindblindness is especially pervasive in the scientific literature. We discuss three limitations of this metaphor: It obscures the fact that both autistic and non autistic individuals contribute to the social and communicative difficulties between them, it carries strong negative connotations, and it may impede the recognition that some autistic behaviors are meaningful and adaptive. Researchers should be mindful of the potential consequences of metaphors.